Knowledge and education to inform evidence-based practice in gastrointestinal nursing: a scoping review. (2nd July 2021) - Munnelly, Stacey; Howard, Victoria; Hall, Veronica; Richardson, James; Kirkbride, Matthew
Abstract : Background: Gastrointestinal (GI) nursing incorporates a plethora of specialisms, involving caring for patients with complex pathologies requiring specialist management and nursing care. GI nurses work across a range of clinical areas and have differing levels of knowledge and skill. However, there are gaps in knowledge specific to GI nursing, and there are barriers to education and evidence-based practice (EBP). Innovative educational strategies and the recent development of competency frameworks, such as those for endoscopy and hepatology nursing, have paved the way for other sub-specialisms, yet the different approaches to upskill the workforce require investigation. Aims: This article aims to identify the breadth and depth of research regarding the knowledge and educational needs of GI nurses and to understand the best approach to education and EBP. Methods: A scoping review was performed using the Arksey and O'Malley framework. A search was conducted in two bibliographic databases and across relevant UK organisations. Findings: The database search identified 31 relevant papers published from 2010 to 2021. The studies varied in purpose, method and recommendations, but all reported consistent results, specifically that GI nurses' knowledge requires attention. Many ways were proposed to assess learning needs and educational strategies to improve knowledge and EBP. Conclusion: GI nurses' knowledge requires development, to improve both the confidence and clinical practice of nurses and the experiences and clinical outcomes of patients. The educational and development requirements of GI nurses vary across a wide spectrum of needs and draw on a vast range of resources and evidence bases. Solutions do not need to be expensive or time consuming and can be practical, making use of existing resources and delivered at local, regional and national levels. At the same time, to deliver true EBP, nurses must develop the critical analysis skills required to locate, appraise and organise evidence, interpreting it into the practicalities for decision making. Future researchers should consider exploration of the instruments used to measure EBP and the competence of GI nurses, to evaluate the effectiveness of different educational models and assist educators in the development and refinement of specialist educational programmes.